Overview of Cuba's Food Rationing System - José Alvarez (EDIS)
This fact sheet presents an overview of the history and functioning of Cuba's food rationing system. Issues related to food security are discussed in another fact sheet of this series (EDIS FE483). This is EDIS document FE482, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published July 2004.